MENGGALI KONSEP ALLAH SEBAGAI WUJUD TERTINGGI DALAM RITUS BAU LOLON DAN IMAN KRISTEN - Tokan, Victor (Studi Budaya Nusantara, 2023)
This journal examines one of the Lamaholot traditions, the Bau Lolon rite. Lamaholot is a community and cultural group that inhabits the eastern part of the island of Flores and the three neighboring islands of Adonara, Solor and Lembata. Some villages on the islands of Pantar and Alor are also said to support Lamaholot culture. The Bau Lolon rite is a sacred tradition practiced by the indigenous people of Adonara, East Nusa Tenggara. This ritual symbolizes the unity and togetherness of the Adonara indigenous community, which involves the manifestation of God through the koda, known to the Adonara people as sabda. This ritual is a symbol of respect to the Supreme Being and ancestral spirits. The method used in this research is a comparative study based on books and articles related to the theme. The purpose of writing this article is to review the Bau Lolon rite as a means of manifestation of God known by the Adonara people as Rera Wulan, Tana Ekan. This sign of presence is then analyzed systemically through Thomas Aquinas' theological perspective on the five ways of discovering God's existence. As a result of the research, the concept of God in the Lamaholot